2015
DOI: 10.1177/0148607115612030
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Parenteral Vitamin E Into Conventional Soybean Lipid Emulsion Does Not Prevent Parenteral Nutrition–Associated Liver Disease in Full‐Term Neonatal Piglets

Abstract: In term neonatal piglets, supplemental vitamin E did not prevent cholestasis. Additional vitamin E was not associated with reduced inflammation or oxidative stress. The benefit of supplementing vitamin E into conventional lipid, vs adding fish oil, to prevent early onset of PNALD requires further clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
2
15
1
Order By: Relevance
“…In premature, neonatal piglets administered TPN containing SO-LE at 5 g/kg/d, α-tocopherol supplemented to concentrations present in FO-LE prevented an increase in direct bilirubin and bile acid concentrations, similar to the effect of FO-LE in the study [29]. In two term neonatal piglet TPN studies where SO-LE was given at a higher lipid load (10 g/kg/d), supplemental vitamin E, as α-tocopherol, failed to prevent PNAC based on serum conjugated bilirubin and serum bile acid levels [83,106]. An interesting observation made in both studies, was that the vitamin E supplemented groups showed no change in serum markers of oxidant stress relative to the standard SO-LE treatment groups.…”
Section: Vitamin Esupporting
confidence: 58%
See 1 more Smart Citation
“…In premature, neonatal piglets administered TPN containing SO-LE at 5 g/kg/d, α-tocopherol supplemented to concentrations present in FO-LE prevented an increase in direct bilirubin and bile acid concentrations, similar to the effect of FO-LE in the study [29]. In two term neonatal piglet TPN studies where SO-LE was given at a higher lipid load (10 g/kg/d), supplemental vitamin E, as α-tocopherol, failed to prevent PNAC based on serum conjugated bilirubin and serum bile acid levels [83,106]. An interesting observation made in both studies, was that the vitamin E supplemented groups showed no change in serum markers of oxidant stress relative to the standard SO-LE treatment groups.…”
Section: Vitamin Esupporting
confidence: 58%
“…Given this, the piglet has been a very useful model for studying neonatal PNAC development because of their large birth size and their metabolic needs are closer to that of humans. Piglets develop cholestasis from TPN within 2 weeks of SO-LE administration similar to human infants receiving TPN [ 51 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. In piglets, this does not require the addition of any type of inflammatory insult, such as DSS.…”
Section: Lipid Emulsion Composition and Clinical Effectsmentioning
confidence: 99%
“…At the same lipid dose of 5 g/(kg·d), we recently showed prevention of cholestasis in preterm piglets by supplementing IL with vitamin E to a concentration equivalent to that present in OV (32). However, a recent publication in term piglets administered IL supplemented with vitamin E at 10 g/(kg·d) failed to show any effect on treatment (50). In this study, there were no changes in oxidative markers in piglets as well, even with an elevated serum vitamin E concentration in the supplemented compared with control group.…”
Section: Discussionmentioning
confidence: 94%
“…This group did show that SO-mediated deficits in bile acid clearance were ameliorated by adding α-tocopherol to a commercial SO [21]. However, similar studies performed by Muto et al in a neonatal piglet model of IFALD showed no improvements in bile flow, serum bile acid concentration, or serum direct bilirubin levels with the addition of α-tocopherol to a commercially available SO emulsion [28].…”
Section: Discussionmentioning
confidence: 99%